2017
DOI: 10.21577/0103-5053.20170017
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Silica Nanoparticles Surface to Increase Drug Load and Enhance Bactericidal Response

Abstract: Nanoparticles' surface properties can be used as triggers to regulate or even enhance biological response and generate tailored structures to substitute conventional antibiotics. Here, silica nanoparticles surface was duly tuned in order to increase the water-insoluble drug load (curcumin) and improve the antibacterial activity. Our main motivation was based on the electrostatic attraction between the positively charged amino groups and the negatively charged curcumin and/or bacteria membrane. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Hue et al 53 reported that the interaction among cationic amino groups and anions on the bacterial wall accelerates bacterial death. Similar research by Oliviera et al 54 analyzed the antimicrobial activity of silica nanoparticles functionalized with different amine percentages to measure their ζ-potential and reported that positive surface charge was sufficient for the antimicrobial properties of the nanoparticles. Rokicka-Konieczna et al 55 have done similar studies and Abbaszadegan et al 56 also confirmed the positive effect of nanoparticle surface charge; thereby, our findings are consistent with the previous reports, and the existence of amine groups is the main key to bacterial growth inhibition.…”
Section: Resultsmentioning
confidence: 68%
“…Hue et al 53 reported that the interaction among cationic amino groups and anions on the bacterial wall accelerates bacterial death. Similar research by Oliviera et al 54 analyzed the antimicrobial activity of silica nanoparticles functionalized with different amine percentages to measure their ζ-potential and reported that positive surface charge was sufficient for the antimicrobial properties of the nanoparticles. Rokicka-Konieczna et al 55 have done similar studies and Abbaszadegan et al 56 also confirmed the positive effect of nanoparticle surface charge; thereby, our findings are consistent with the previous reports, and the existence of amine groups is the main key to bacterial growth inhibition.…”
Section: Resultsmentioning
confidence: 68%
“…Mesoporous silica and organosilica nanomaterials have been applied for antimicrobial applications with different approaches. The first approach involved the transportation of antimicrobial molecular or macromolecular agents via MSNs. The incorporation of antimicrobial ionic liquids inside the mesopores of the particles was achieved in high content by Lin and co‐workers by simply using the ionic liquid as a structure‐templating agent for the synthesis of the particles .…”
Section: Trends In Biomedical Applicationsmentioning
confidence: 99%
“…Briefly, TPEP derivatives were loaded into silica nanoparticles (TPEP-SiO 2 ) according to the modified synthetic procedures [ 24 ]. In 100 mL round bottom flask, a mixture of 1 mL of TEOS, 32 mL of ethanol and 0.26 mL of TPEP derivatives solution in ethanol were added.…”
Section: Methodsmentioning
confidence: 99%